2019
DOI: 10.1111/acer.14249
|View full text |Cite
|
Sign up to set email alerts
|

Addiction‐Focused Eye Movement Desensitization and Reprocessing Therapy as an Adjunct to Regular Outpatient Treatment for Alcohol Use Disorder: Results From a Randomized Clinical Trial

Abstract: BackgroundThis study examined the feasibility, safety, and efficacy of addiction‐focused eye movement desensitization and reprocessing (AF‐EMDR) treatment, as an add‐on intervention to treatment as usual (TAU).MethodsAdult outpatients with alcohol use disorder (AUD) (N = 109) who already received or had just started with TAU (Community Reinforcement Approach) were recruited at 6 outpatient addiction care facilities. They were randomly assigned to either TAU + 7 weekly 90‐minute sessions of AF‐EMDR (N = 55) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
7
0
2
Order By: Relevance
“…Eight RCT (out of 27), Two control-groups (out of 10) and three (out of 12) group studies reported that patients had stopped the EMDR sessions before completion of treatment. In particular, high levels of drop-out in a single study were reported in the treatment of addictions [number of dropouts, Addictions ( n = 19; Markus et al, 2020 )], OCD ( n = 17; Nazari et al, 2011 ), and Pain ( n = 12; Mazzola et al, 2009 ). Overall, the reasons for drop-out, when specified and explicitly related to the treatment, were usually because of how hard it is to reminisce past memories, or to EMDR being time-consuming (e.g., Markus et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight RCT (out of 27), Two control-groups (out of 10) and three (out of 12) group studies reported that patients had stopped the EMDR sessions before completion of treatment. In particular, high levels of drop-out in a single study were reported in the treatment of addictions [number of dropouts, Addictions ( n = 19; Markus et al, 2020 )], OCD ( n = 17; Nazari et al, 2011 ), and Pain ( n = 12; Mazzola et al, 2009 ). Overall, the reasons for drop-out, when specified and explicitly related to the treatment, were usually because of how hard it is to reminisce past memories, or to EMDR being time-consuming (e.g., Markus et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent RCT tested the adjunction of EMDR in addition to TAU in a randomised group of adult patients with alcohol use disorder (Markus et al, 2020 ). The study failed to demonstrate any additive effects in the TAU+EMDR group; possibly due to the population tested being chronic poly-morbid patients with poor social support.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indicadores Evidencia** Científico "Este estudio se centra en el potencial de la terapia de desensibilización y reprocesamiento de los movimientos oculares (EMDR), como una intervención adicional al tratamiento regular de la adicción" (Markus et al, 2019). "Además de los numerosos estudios de control de casos, ahora también hay disponibles seis ensayos clínicos controlados aleatorios que demuestran la eficacia y la seguridad de la EMDR en el tratamiento de diferentes afecciones de dolor" (Tesarz, Wicking, Bernardy & Seidler, (2019).…”
Section: Dominiounclassified
“…Actualiza su información, la EMDR, desde su creación, ha sido objeto de experimentación (Cotter et al, 2017;Covers et al, 2019;Hegarty et al, 2016), a través de sus estudios, han actualizado la información de su eficacia y validez, lo que conlleva la modificación de datos, hipótesis y teorías, incluso con respecto a otros enfoques. Busca comentarios críticos de otros, no se opone a las críticas de otras corrientes o de sus detractores, al contrario, las toma en cuenta para sus estudios de validez y efectividad (Brennstuhl y Bassan, 2018;Jahanfar et al, 2020;Markus et al, 2019).…”
Section: Pseucientíficounclassified